OHP-045 Incidence and risk factors of adverse drug reactions in the general population observed through an active pharmacovigilance project. (24th February 2014) - Stabile, S; Ruggiero, F; Taurasi, F; Vigano, M; Borin, F
Abstract : Background: Medicines use will probably increase due to an ageing population, the increasing use of drugs for prevention, the development of new medicines and especially the transition of prescription drugs to over-the-counter availability. The monitoring of adverse drug reactions (ADRs) is essential, in part to increase our knowledge of drug safety profiles and their risk factors. Purpose: To systematically evaluate adverse drug reactions (ADRs) in the general populations during a 6-month period of observation. Materials and methods: For this study all potential ADRs were systematically recorded among all patients hospitalised in three Hospitals of A. O. Salvini including all in the emergency department. All cases were validated by physicians for preventability, seriousness, resolution and active ingredients. Results: During the observation period 405 ADRs were observed with a severity rate of 25.43%. The ADR severity rate for the paediatric population was 16.54% without significant differences between the sexes, while for the adult patients (≥18 years) the severity increased to 29.50% and with a higher incidence of ADRs in females (55.57%). The System Organ Classification (SOC) most frequently reported is skin and subcutaneous reaction: in the adult population it represented 55.47% overall and 46.38% of severe ADRs. Nervous System Diseases were the second most-reported severe ADRs in over-18s (13.04%) followed by Metabolism and Nutrition Disorders (7.24%) mainly represented by iatrogenic episodes of hypoglycaemia. The most common drugs reported for ADRs in adults were antibiotics (29.45%), NSAIDS (16.50%) and contrast media (7.12%). Anticoagulants were 6.15%. Conclusions: Age and female sex are confirmed as risk factors for ADRs. The largest proportion of ADRs was due to allergic and non-preventable reactions, but there was also a significant quota of preventable severe ADRs such as iatrogenic hypoglycaemias. Training in correct drug use, both for physician and patients, could help to minimise the incidence of ADRs. No conflict of interest.